2018
DOI: 10.1007/s13361-018-2019-6
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectral Detection of Forward- and Reverse-Hydrogen/Deuterium Exchange Resulting from Residual Solvent Vapors in Electrospray Sources

Abstract: Characterizing glycans is analytically challenging since glycans are heterogeneous, branched polymers with different three-dimensional conformations. Hydrogen/deuterium exchange-mass spectrometry (HDX-MS) has been used to analyze native conformations and dynamics of biomolecules by measuring the mass increase of analytes as labile protons are replaced with deuterium following exposure to deuterated solvents. The rate of exchange is dependent on the chemical functional group, the presence of hydrogen bonds, pH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…Knowledge the overall effect of experimental factors will guide evaluation of the measurement uncertainty. One possible error could arise if the deuterium content of peptides varies as a function of charge. , Thus, deuterium content of centroids versus peptide charge was examined for 513 peptides ( z = +1 to +7) of 106 sequences reported by 13 laboratories. No evidence of systemic, in-ESI source, intermolecular H/D exchange was observed (Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge the overall effect of experimental factors will guide evaluation of the measurement uncertainty. One possible error could arise if the deuterium content of peptides varies as a function of charge. , Thus, deuterium content of centroids versus peptide charge was examined for 513 peptides ( z = +1 to +7) of 106 sequences reported by 13 laboratories. No evidence of systemic, in-ESI source, intermolecular H/D exchange was observed (Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…ESI parameters were spray voltage: 3.5 kV, sheath gas: 12 arb units, auxiliary gas: 0 arb units, and capillary temperature 300 °C. Between runs, the source was kept open for 2 min to prevent solvent vapor build-up . Undeuterated spectra were collected with neither the metal plate nor D 2 O droplet inside the ESI source.…”
Section: Methodsmentioning
confidence: 99%
“…Application of the hydrogen/deuterium exchange for investigating carbohydrates was previously reported [ 17 , 18 , 19 , 20 ]. E. Gallagher showed that it was possible to distinguish three different carbohydrate isomers using the H/D exchange reaction [ 21 ].…”
Section: Introductionmentioning
confidence: 99%